Method for preparing nanosheet array material and positive pole piece
By preparing nanosheet array materials with a mesh structure and applying them to the functional material layer of the positive electrode sheet of lithium-ion battery, the problems of increased internal resistance and reduced discharge capacity caused by the increase in the load of the positive electrode sheet are solved, and a higher charge and discharge cycle life and electrochemical motion efficiency are achieved.
Patent Information
- Application Number
- CN202411761641.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The increase in the positive electrode load of existing lithium-ion batteries leads to an increase in internal resistance and a decrease in discharge capacity, making it difficult to meet the needs of high-performance applications such as new energy vehicles.
A method of preparing nanosheet array material is adopted. By mixing and heating the fatty amine solution and intermediate solution, an amide composite is obtained, and a carbon-containing composite is formed by calcining treatment, and finally mixed with the iron metal salt aqueous solution to prepare a nanosheet array material with a network structure. This material is used for the functional material layer of the positive electrode sheet, reducing the polarization internal resistance between the interface between the positive electrode material layer and the positive electrode current collector.
By introducing nanosheet array material into the positive electrode sheet, the polarization internal resistance between the interface between the positive electrode material layer and the positive electrode current collector is significantly reduced, the movement efficiency of lithium ions in the electrochemical process is improved, and the charging and discharging cycle life of the battery is extended.
Smart Images

Figure CN119581529A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium battery technology, and in particular, to a method for preparing a nanosheet array material and a positive electrode sheet. Background Art
[0002] As energy storage devices, lithium-ion batteries have been widely used in portable electronic devices, new energy vehicles and other fields. In particular, with the popularity of new energy vehicles in recent years, people have put forward higher requirements for the safety performance and cycle performance of lithium-ion batteries. At present, in order to further improve the performance of lithium-ion batteries and expand the application scenarios of lithium-ion batteries, existing research is exploring from different angles such as reducing the production cost of lithium batteries and extending the service life of lithium batteries. Summary of the invention
[0003] In the first aspect of the present application, a method for preparing a nanosheet array material is proposed, comprising: mixing and heating a fatty amine solution with an intermediate solution to obtain an amide complex, wherein the intermediate solution comprises a copper metal salt, a dicarboxylic acid, and an alcohol solvent; calcining the amide complex to obtain a carbon-containing complex; and mixing the carbon-containing complex with an aqueous solution of an iron metal salt to obtain the nanosheet array material.
[0004] Thus, a nanosheet array material with a network structure can be prepared. The nanosheet array material has excellent electrical conductivity and a spatial structure with a high specific area, and can optimize the movement of lithium ions in the electrochemical process of a lithium battery.
[0005] In some embodiments, the fatty amine solution includes fatty amine and a non-protonic polar solvent, wherein the fatty amine includes at least one of ethylenediamine, dimethylamine, laurylamine, ethanolamine, and hexamethylenediamine. Thus, the fatty amine can undergo polycondensation in the non-protonic polar solvent, and the reaction process is relatively controllable, which is conducive to controlling the morphology of the prepared nanosheet array material.
[0006] In some embodiments, in the fatty amine solution, the molar volume ratio of the fatty amine to the aprotic polar solvent is 0.001 mmol / mL-0.002 mmol / mL. Thus, the fatty amines in the fatty amine solution can be separated from each other, which is conducive to the formation of an amide complex with a lower degree of spatial aggregation.
[0007] In some embodiments, the aprotic polar solvent includes at least one of acetonitrile, dimethylformamide, dimethyl sulfoxide, and hexamethylphosphoric triamide. Thus, the aprotic polar solvent is conducive to mixing and heating under relatively mild reaction conditions to prepare the amide complex.
[0008] In some embodiments, the dicarboxylic acid includes at least one of succinic acid, adipic acid, maleic acid, and fumaric acid, thereby facilitating the formation of a structurally stable amide complex.
[0009] In some embodiments, the copper metal salt includes at least one of copper chloride, copper sulfate, copper nitrate, and copper acetate. Thus, the molecular spatial configuration of the amide complex can be adjusted.
[0010] In some embodiments, the iron metal salt aqueous solution includes an iron metal salt, wherein the iron metal salt includes at least one of ferric chloride and ferric nitrate. The iron metal salt releases iron ions in water, and the iron ions have reducing properties, which can reduce the copper ions in the amide complex to metallic copper, which is beneficial to remove the copper element from the prepared nanosheet array material. Thus, it is beneficial to improve the purity of the prepared nanosheet array material.
[0011] In some embodiments, the molar concentration of the aqueous solution of the iron metal salt is 0.2 mol / L-0.5 mol / L. Thus, a higher reaction efficiency can be achieved.
[0012] In some embodiments, in the intermediate solution, the copper metal salt, the dicarboxylic acid, and the alcohol solution are mixed in a molar volume ratio of (0.09-1.3) mmol: (0.4-0.8) mmol: (50-70) mL. Thus, the intermediate solution is conducive to the preparation of an amide complex having a network structure.
[0013] In some embodiments, the temperature of the mixed heating treatment is 90° C.-120° C., and the time of the mixed heating treatment is 6 h-36 h. This is conducive to the formation of an amide complex with a regular sequence of polymer molecular chains.
[0014] In some embodiments, the stirring rate of the mixing process is 1200 rpm-1800 rpm. The stirring rate of the mixing process is within the aforementioned range, which is beneficial to reduce the aggregation of reactants during the mixing process. Thus, it is beneficial to prepare a nanosheet array material with a mesh structure.
[0015] In some embodiments, the calcination temperature is 500° C.-1500° C., and the calcination time is 0.5 h-3 h. Under the calcination conditions, some molecules in the amide complex decompose to form a carbon-containing complex.
[0016] In some embodiments, the heating rate of the calcination treatment is 1° C. / min-10° C. / min. This is beneficial for preparing a carbon-containing composite having a spatial network structure.
[0017] In some embodiments, the method further comprises: after the mixing and heating treatment, the amide complex is subjected to a heat preservation treatment, wherein the temperature of the heat preservation treatment is 30° C.-80° C., and the time of the mixing and heating treatment is 1 h-5 h. This is conducive to preparing an amide complex with a relatively stable structure.
[0018] In some embodiments, the nanosheet array material is subjected to a vacuum drying process, and the vacuum degree of the vacuum drying process is -70 kPa to -90 kPa.
[0019] In the second aspect of the present application, the present application proposes a positive electrode electrode sheet, comprising: a positive electrode current collector; a functional material layer, the functional material layer is located on at least one side of the positive electrode current collector, wherein the functional material layer includes a nanosheet array material prepared by the method for preparing a nanosheet array material proposed in the present application; a positive electrode material layer, the positive electrode material layer is arranged on a side of the functional material layer away from the positive electrode current collector.
[0020] Therefore, by providing a functional material layer between the positive electrode current collector and the positive electrode material layer, the polarization internal resistance of the interface between the positive electrode material layer and the positive electrode current collector can be reduced, so that the positive electrode plate has a higher charge and discharge cycle life.
[0021] In some embodiments, the thickness of the functional material layer is 6 μm-30 μm. When the thickness of the functional material layer is within the aforementioned range, the functional material layer can be well combined with the positive electrode current collector and the positive electrode material layer.
[0022] In some embodiments, the coverage of the functional material layer on the surface of the positive electrode current collector is 15%-70%, thereby improving the cycle performance of the positive electrode sheet.
[0023] In some embodiments, the functional material layer includes a binder, which is conducive to forming a relatively close bond between the functional material layer, the positive electrode current collector, and the positive electrode material layer.
[0024] In some embodiments, the mass of the binder in the functional material layer is 35%-55%. This is beneficial for obtaining a positive electrode sheet having a functional material layer and a positive electrode material layer with high peel strength, and for improving the cycle life of a battery including the positive electrode sheet.
[0025] In some embodiments, the binder includes at least one of polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polyaniline, polypyrrole, lithium carboxymethyl cellulose or styrene-butadiene rubber. Thus, the peel strength of the functional material layer and the positive electrode material layer on the positive electrode current collector can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0027] Figure 1 This is a schematic diagram of the structure of a positive electrode sheet in one embodiment of the present application;
[0028] Figure 2 This is a scanning electron microscope image of the nanosheet array material in Example 1 of the present application;
[0029] Figure 3 This is a scanning electron microscope image of the nanosheet array material in Example 1 of the present application;
[0030] Figure 4 This is a comparison chart of the cycle performance of the lithium batteries in Example 1 of the present application and Comparative Example 1.
[0031] Description of reference numerals:
[0032] 1. Positive electrode current collector; 2. Functional material layer; 3. Positive electrode material layer. DETAILED DESCRIPTION
[0033] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0034] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0035] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0036] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0040] Lithium-ion batteries have the advantages of no memory effect, good safety performance and environmental friendliness, and are widely used in electronic equipment, power storage stations, new energy vehicles, etc. The preparation of large-capacity lithium batteries can extend the service life of battery equipment. For new energy vehicles, it can increase the cruising range of the car and reduce the user's mileage anxiety. Methods for increasing the capacity of lithium batteries include increasing the load of the positive electrode plate. However, the increase in the thickness of the positive electrode plate caused by the increase in the load of the positive electrode plate makes it more difficult for the lithium battery electrolyte to infiltrate the positive electrode plate, resulting in difficulty in the embedding and extraction of lithium ions, further resulting in an increase in the internal resistance of the lithium battery and a decrease in the discharge capacity. Therefore, in order to solve the problem of the aforementioned high-load positive electrode plate, the present application proposes a method for preparing a nanosheet array material. The nanosheet array material prepared by this method can be used in the functional material layer of the positive electrode plate, which is beneficial to reduce the internal resistance of the positive electrode plate and delay the service life of the battery. The method and positive electrode plate.
[0041] In the first aspect of the present application, a method for preparing a nanosheet array material is proposed, comprising: mixing and heating a fatty amine solution with an intermediate solution to obtain an amide complex, wherein the intermediate solution comprises a copper metal salt, a dicarboxylic acid, and an alcohol solvent; calcining the amide complex to obtain a carbon-containing complex; and mixing the carbon-containing complex with an aqueous solution of an iron metal salt to obtain the nanosheet array material.
[0042] The method for preparing a nanosheet array material proposed in the present application introduces cations into the structure of the amide complex molecule during the composite process of forming amides to prepare an amide polymer containing copper ions. The amide complex is subjected to calcination treatment, and the polymer molecular chain undergoes a certain degree of decomposition to form a carbon-containing complex with a spatial network structure. Through the reduction of iron ions in an iron metal salt in a solution, the copper ions are reduced to metallic copper to obtain the nanosheet array material. Thus, a nanosheet array material with a network structure can be prepared, and the nanosheet array material has excellent electrical conductivity and a spatial structure with a high specific area, which can optimize the movement of lithium ions in the electrochemical process of lithium batteries.
[0043] In some embodiments, the fatty amine solution includes a fatty amine and a non-protonic polar solvent, wherein the fatty amine includes at least one of ethylenediamine, dimethylamine, laurylamine, ethanolamine, and hexamethylenediamine.
[0044] The aforementioned fatty amine has a relatively regular molecular structure, which is conducive to the preparation of an amide complex with a relatively orderly molecular structure. The use of an aprotic polar solvent as a solvent is conducive to the mixed heating treatment being carried out under relatively mild conditions, making the reaction process more controllable. Thus, it is conducive to the preparation of a nanosheet array material with a mesh structure.
[0045] In some embodiments, in the fatty amine solution, the molar volume ratio of the fatty amine to the aprotic polar solvent is 0.001mmol / mL-0.002mmol / mL. The molecules of the fatty amine have a certain molecular weight and spatial volume, and the molar volume ratio of the fatty amine to the aprotic polar solvent is within the aforementioned range, which is conducive to the full dispersion of the fatty amine in the aprotic polar solvent. As a result, the fatty amines in the fatty amine solution can be separated from each other, which is conducive to the generation of an amide complex with a low degree of spatial aggregation.
[0046] In some embodiments, the aprotic polar solvent includes at least one of acetonitrile, dimethylformamide, dimethyl sulfoxide, and hexamethylphosphoric triamide. Low-temperature polycondensation can occur in the aprotic polar solvent. Therefore, the use of the aprotic polar solvent is conducive to mixing and heating under relatively mild reaction conditions to prepare the amide complex.
[0047] In some embodiments, the dicarboxylic acid includes at least one of butenedioic acid, adipic acid, maleic acid, and fumaric acid. The dicarboxylic acid can undergo coordination reaction with copper ions in copper metal salts and can undergo solution polymerization with fatty amines in fatty amine solutions, thereby facilitating the formation of a structurally stable amide complex.
[0048] In some embodiments, the copper metal salt includes at least one of copper chloride, copper sulfate, copper nitrate, and copper acetate. The copper metal salt can produce copper ions in an alcohol solution. The copper ions, as the central atom forming a coordination bond, affect the molecular structure of the generated amide complex, which is conducive to forming a spatial configuration with a certain distance between molecular chains. Thus, the molecular spatial configuration of the amide complex can be adjusted.
[0049] In some embodiments, the iron metal salt aqueous solution includes an iron metal salt, wherein the iron metal salt includes at least one of ferric chloride and ferric nitrate. The iron metal salt releases iron ions in water, and the iron ions have reducing properties, which can reduce the copper ions in the amide complex to metallic copper, which is beneficial to remove the copper element from the prepared nanosheet array material. Thus, it is beneficial to improve the purity of the prepared nanosheet array material.
[0050] In some embodiments, the molar concentration of the iron metal salt aqueous solution is 0.2 mol / L-0.5 mol / L. Within the molar concentration range of the iron metal salt aqueous solution, the iron ions can sufficiently reduce the copper ions, thereby achieving a higher reaction efficiency.
[0051] In some embodiments, in the intermediate solution, the copper metal salt, the dicarboxylic acid, and the alcohol solution are mixed according to a molar volume ratio of (0.09-1.3) mmol: (0.4-0.8) mmol: (50-70) mL. Mixing within the aforementioned molar volume ratio range, the copper ions in the copper metal salt enter the alcohol solvent, the copper ions and the dicarboxylic acid molecules form an intermediate connected by a coordination bond, and the intermediate in the intermediate solution can maintain a relatively sparse distribution. Thus, the intermediate solution is conducive to the preparation of an amide complex with a network structure.
[0052] In some embodiments, the temperature of the mixed heating treatment is 90°C-120°C, and the time of the mixed heating treatment is 6h-36h. Under the aforementioned mixed heating treatment conditions, the fatty amine in the fatty amine solution and the dicarboxylic acid in the intermediate solution undergo a solution polycondensation reaction, and the reaction process of the solution polycondensation is relatively controllable. This is conducive to the formation of an amide complex with a regular sequence polymer molecular chain.
[0053] In some embodiments, the stirring rate of the mixing process is 1200 rpm-1800 rpm. The stirring rate of the mixing process is within the aforementioned range, which is beneficial to reduce the aggregation of reactants during the mixing process. Thus, it is beneficial to prepare a nanosheet array material with a mesh structure.
[0054] In some embodiments, the calcination temperature is 500° C.-1500° C., and the calcination time is 0.5 h-3 h. Under the calcination conditions, some molecules in the amide complex decompose to form a carbon-containing complex.
[0055] In some embodiments, the heating rate of the calcination treatment is 1° C. / min-10° C. / min. This is beneficial for preparing a carbon-containing composite having a spatial network structure.
[0056] In some embodiments, the method further comprises: after the mixing and heating treatment, the amide complex is subjected to a heat preservation treatment, wherein the temperature of the heat preservation treatment is 30° C.-80° C., and the time of the mixing and heating treatment is 1 h-5 h. This is conducive to preparing an amide complex with a relatively stable structure.
[0057] In some embodiments, the nanosheet array material is subjected to a vacuum drying process, and the vacuum degree of the vacuum drying process is -70 kPa to -90 kPa.
[0058] In some embodiments, the method further comprises: performing the calcination treatment in a protective atmosphere, wherein the protective atmosphere comprises at least one of an inert gas and nitrogen.
[0059] In the second aspect of the present application, the present application proposes a positive electrode electrode sheet, comprising: a positive electrode current collector; a functional material layer, the functional material layer is located on at least one side of the positive electrode current collector, wherein the functional material layer includes a nanosheet array material prepared by the method for preparing a nanosheet array material proposed in the present application; a positive electrode material layer, the positive electrode material layer is arranged on a side of the functional material layer away from the positive electrode current collector.
[0060] The positive electrode sheet proposed in this application includes a functional material layer, referring to Figure 1 The functional material layer is disposed between the positive electrode current collector and the positive electrode material layer. The functional material layer comprises a nanosheet array material prepared by the method for preparing a nanosheet array material proposed in the present application. Figure 2 and Figure 3The amorphous nanosheets in the nanosheet array material are arranged in an interlaced manner, providing a large number of active sites for rapid insertion and extraction of lithium ions in the surface and interlayer gaps of the multilayered nanosheets. The mesh morphology of the nanosheets has a high specific surface area, which is conducive to improving the ion transport and diffusion path at the solid-liquid interface in lithium electrons, increasing the charge transfer rate, and improving the reaction rate of the lithium ion desolvation process, thereby reducing the polarization internal resistance of the interface between the positive electrode material layer and the positive electrode current collector, and optimizing the lithium ion transport process in the positive electrode sheet.
[0061] Therefore, by providing a functional material layer between the positive electrode current collector and the positive electrode material layer, the polarization internal resistance of the interface between the positive electrode material layer and the positive electrode current collector can be reduced, so that the positive electrode plate has a higher charge and discharge cycle life.
[0062] In some embodiments, the thickness of the functional material layer is 6 μm-30 μm. When the thickness of the functional material layer is within the aforementioned range, the functional material layer can be well combined with the positive electrode current collector and the positive electrode material layer.
[0063] In some embodiments, the coverage of the functional material layer on the surface of the positive electrode current collector is 15%-70%.
[0064] The coverage of the functional material layer on the surface of the positive electrode current collector is the ratio of the area of the functional material layer to the area of the corresponding surface of the positive electrode current collector on which the functional material layer is disposed. The coverage within the aforementioned range can better improve the lithium ion transmission and diffusion path. Thus, the cycle performance of the positive electrode sheet can be better improved.
[0065] In some embodiments, the functional material layer includes a binder. The binder in the functional material layer can form a relatively stable functional material layer structure with the nanosheet array material, and provide bonding force between the functional material layer and the positive electrode current collector and the positive electrode material layer. This is conducive to forming a relatively tight bond between the functional material layer and the positive electrode current collector and the positive electrode material layer.
[0066] In some embodiments, the mass of the binder in the functional material layer is 35%-55%.
[0067] The mass of the binder in the functional material layer is within the aforementioned range, which can provide sufficient support for the improved mesh nanosheet array material in the functional material layer, and reduce the damage to the electrolyte transmission channels caused by the displacement of particles in the mesh nanosheet array material. In addition, after multiple charge and discharge processes, the structure of the positive electrode material layer changes due to the displacement of ions in the material. The bonding force provided by the binder to the positive electrode material layer is conducive to improving the stability of the positive electrode plate structure. As a result, it is beneficial to have a positive electrode plate with a higher peel strength functional material layer and a positive electrode material layer, and it is beneficial to improve the cycle life of the battery containing the positive electrode plate.
[0068] In some embodiments, the binder includes at least one of polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polyaniline, polypyrrole, lithium carboxymethyl cellulose or styrene-butadiene rubber. In the functional material layer, the molecular chain segments of the binder have rich functional group structures and chemical bonding sites, and can be effectively anchored on the surface of the active material, nanosheet array material, conductive agent and positive electrode current collector, forming a tight bond between the positive electrode material layer and the positive electrode current collector. In this way, the peel strength of the functional material layer and the positive electrode material layer on the positive electrode current collector can be improved.
[0069] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0070] Example 1
[0071] Functional material synthesis:
[0072] Step 1: Dissolve 1.2 mmol of ethylenediamine in 70 mL of dimethylformamide and stir thoroughly until clear, which is referred to as solution A; dissolve 0.1 mmol of copper chloride dihydrate and 0.9 mmol of butenedioic acid in 90 mL of ethanol, which is referred to as solution B;
[0073] Step 2: Mix solution A and solution B under high-speed stirring, stir for 15 minutes, pour the mixed solution into the reactor, heat to 100°C and react for 24 hours. After the reaction is completed, place the reactor at 50°C for 2 hours and then cool naturally to room temperature. The obtained product is filtered and washed with anhydrous ethanol. The washed product is vacuum dried to obtain a powdered amide complex;
[0074] Step 3: calcining the powdered amide complex in an inert atmosphere at a calcination temperature of 1200° C., a calcination time of 1.5 h, and a heating rate of 2° C. / min. After calcination, a carbon-containing complex is obtained, and the mixture is naturally cooled to room temperature.
[0075] Step 4: Add the calcined powder into a 0.3 mol / L ferric chloride solution and stir thoroughly for 8 hours. After the reaction is completed, filter and wash the product with deionized water, and vacuum dry it to obtain a nanosheet array material.
[0076] Battery preparation:
[0077] Preparation of the functional material layer: According to the mass ratio, 7% polyvinylidene fluoride and 93% nanosheet array material were added into N-methylpyrrolidone solvent, and after sufficient stirring and dispersion, a functional material layer slurry was obtained.
[0078] Preparation of positive electrode plates: Disperse and mix the positive electrode material lithium iron phosphate LiFePO4 with conductive carbon black SP, conductive carbon nanotubes CNTs, and binder polyvinylidene fluoride PVDF in a mass ratio of 97:1.2:0.5:1.3, add organic solvent N-methylpyrrolidone for high-speed stirring, and adjust the viscosity and solid content. After high-speed stirring, vacuum defoaming is performed in a stirring tank to obtain positive electrode material slurry. Finally, the functional material layer slurry and the positive electrode material slurry are successively coated on the surfaces of both sides of the 13μm aluminum foil by a coating machine, and then dried, rolled, slit, and die-cut to form positive electrode plates of the required specifications and sizes. The positive electrode plate includes a functional material layer and a positive electrode material layer, wherein the compaction density of the coated positive electrode material layer is 2.5g / cm 3 .
[0079] Preparation of negative electrode sheets: Disperse and mix the negative electrode active material graphite with the conductive carbon black SP, binder styrene butadiene rubber SBR, and thickener carboxymethyl cellulose CMC in a mass ratio of 96.5:1.2:1.5:0.8, add deionized water for high-speed stirring, and adjust the viscosity and solid content. After high-speed stirring, vacuum defoaming is performed in the stirring tank to obtain a uniformly dispersed negative electrode slurry. The negative electrode slurry is coated on both sides of the 6μm copper foil by a coating machine, and after drying, rolling, striping, and die-cutting, it is made into negative electrode sheets of the required specifications and sizes. The compaction density of the coated negative electrode material layer is 1.6g / cm 3 .
[0080] Assemble the battery: Assemble the positive electrode plate, negative electrode plate and separator in a "Z"-shaped stacking method, and connect the pole ears by ultrasonic welding. Put the welded core into aluminum-plastic film for top / side sealing, and reserve the injection port and air bag. Inject the electrolyte according to the injection coefficient of 2.5g / Ah (the solvent includes: ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 1:2:1 (v / v), lithium salt 13wt% LiPF6, additives 1wt% vinylene carbonate VC and 2wt% vinyl sulfate DTD). After sealing, infiltration, formation, and vacuuming, the lithium-ion battery is finally obtained.
[0081] Comparative Example 1
[0082] Comparative Example 1 is consistent with Example 1, except that the positive electrode plate in Comparative Example 1 does not include a functional material layer.
[0083] Test method:
[0084] To ensure the reliability of the battery test results, two lithium-ion batteries were tested synchronously and in parallel, and were named Comparative Example 1 (battery No. 1) and Comparative Example 1 (battery No. 2) respectively.
[0085] The lithium-ion battery assembled as described above was charged / discharged for 3 cycles at a rate of 0.33C, and then fully charged to 100% battery state of charge (SoC state). Under a 25°C environment, the cycle test was performed according to the 0.5C charge (constant current-constant voltage) / 1C discharge (constant current) process step. To ensure the reliability of the battery test results, two lithium-ion batteries were tested in parallel, and they were named Example 1 (battery No. 1) and Example 1 (battery No. 2), respectively.
[0086] Test results:
[0087] The cycle performance of Example 1 and Comparative Example 1 can be specifically referred to Figure 4 It can be found that after 30 charge-discharge cycles, the capacity retention rate of the two lithium-ion batteries in Example 1 is significantly better than that of the two lithium-ion batteries in Comparative Example 1. This result shows that by providing a functional material layer between the positive electrode current collector and the positive electrode material layer, the polarization internal resistance at the interface between the positive electrode material layer and the positive electrode current collector can be reduced, which has an improvement effect on increasing the charge-discharge cycle life of the positive electrode sheet.
[0088] In the description of the present application, it should be understood that the terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0089] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0090] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0091] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a nanosheet array material, characterized in that: include: The fatty amine solution and the intermediate solution are mixed and heated to obtain an amide complex, wherein the intermediate solution comprises a copper metal salt, a dicarboxylic acid, and an alcohol solvent; calcining the amide complex to obtain a carbon-containing complex; The carbon-containing composite is mixed with an aqueous solution of an iron metal salt to obtain the nanosheet array material.
2. The method according to claim 1, characterized in that: The fatty amine solution comprises a fatty amine and a non-protonic polar solvent, wherein the fatty amine comprises at least one of ethylenediamine, dimethylamine, laurylamine, ethanolamine and hexamethylenediamine; and / or, In the fatty amine solution, the molar volume ratio of the fatty amine to the aprotic polar solvent is 0.001 mmol / mL-0.002 mmol / mL; and / or, The aprotic polar solvent includes at least one of acetonitrile, dimethylformamide, dimethyl sulfoxide, and hexamethylphosphoric triamide.
3. The method according to claim 1, characterized in that: The dicarboxylic acid comprises at least one of butenedioic acid, adipic acid, maleic acid and fumaric acid; and / or, The copper metal salt includes at least one of copper chloride, copper sulfate, copper nitrate and copper acetate.
4. The method according to claim 1, characterized in that: The iron metal salt aqueous solution comprises an iron metal salt, wherein the iron metal salt comprises at least one of ferric chloride and ferric nitrate; and / or, The molar concentration of the iron metal salt aqueous solution is 0.2 mol / L-0.5 mol / L.
5. The method according to any one of claims 1 to 3, characterized in that: In the intermediate solution, the copper metal salt, the dicarboxylic acid, and the alcohol solution are mixed according to a molar volume ratio of (0.09-1.3) mmol: (0.4-0.8) mmol: (50-70) mL.
6. The method according to any one of claims 1 to 3, characterized in that: The temperature of the mixed heating treatment is 90°C-120°C, and the time of the mixed heating treatment is 6h-36h; and / or, The stirring rate of the mixing process is 1200rpm-1800rpm; and / or, The calcination temperature is 500°C-1500°C, and the calcination time is 0.5h-3h; and / or, The heating rate of the calcination treatment is 1°C / min-10°C / min.
7. The method according to any one of claims 1 to 3, characterized in that: Further including: After the mixed heating treatment, the amide complex is subjected to a heat preservation treatment, wherein the temperature of the heat preservation treatment is 30° C.-80° C., and the time of the mixed heating treatment is 1 h-5 h; and / or, The nanosheet array material is subjected to a vacuum drying process, wherein the vacuum degree of the vacuum drying process is -70 kPa to -90 kPa.
8. A positive electrode sheet, characterized in that: include: Positive electrode current collector; A functional material layer, the functional material layer being located on at least one side of the positive electrode current collector, wherein the functional material layer comprises a nanosheet array material prepared by the method according to any one of claims 1 to 7; A positive electrode material layer is disposed on a side of the functional material layer away from the positive electrode current collector.
9. The positive electrode sheet according to claim 8, characterized in that: The thickness of the functional material layer is 6 μm-30 μm; and / or, The coverage rate of the functional material layer on the surface of the positive electrode current collector is 15%-70%.
10. The positive electrode sheet according to claim 9, characterized in that: The functional material layer further includes a binder, Wherein, the mass of the binder in the functional material layer is 35%-55%; and / or, The binder includes at least one of polyacrylic acid, polyacrylonitrile, polyvinyl alcohol, polyaniline, polypyrrole, lithium carboxymethyl cellulose or styrene-butadiene rubber.